Multidetector computed tomography in the diagnosis of spontaneous isolated superior mesenteric artery dissection: changes in diameter on nonenhanced scan and stent treatment follow-up. Issue 12 (December 2019) - Yan, Weiqiang; Huang, Rong; Shi, Qiao; Shan, Huiming; Zhu, Yi; Cheng, Guanxun; Quan, Xianyue
Objective: This study was performed to assess the changes in diameter of the superior mesenteric artery (SMA) in patients with spontaneous isolated SMA dissection (SISMAD) on nonenhanced multidetector computed tomography (MDCT) and determine the clinical value of follow-up MDCT after endovascular stent placement (ESP). Methods: The diameters of the SMA and superior mesenteric vein (SMV) as measured on nonenhanced MDCT were compared between 20 patients with SISMAD and 20 control subjects. ESP was performed in 14 patients with SISMAD, and follow-up MDCT was performed after ESP. Results: The mean diameter of the SMA in the SISMAD group and control group was 11.69 ± 1.26 and 7.10 ± 0.97 mm, respectively, with a statistically significant difference. The SMA diameters were even larger than the SMV diameters. Follow-up MDCT showed stent patency in 13 patients and occlusion in 1 patient. Conclusions: An enlarged diameter of the SMA on nonenhanced MDCT is an important finding for diagnosis of SISMAD, and MDCT is a valuable follow-up method after ESP for SISMAD.